Water crisis - beyond the destruction - Bakas, T.; Papadimitriou, Ι.; Xeroheimonas, I.; Mariolis, D.; Megas, P.; Argyri, P. (Open Schools Journal for Open Science, 2020)
A major issue related to the environment, is namely the lack of water and in general the reduction of clean water supplies over time, mostly in our days due to climate change. Through the projection of scientific data, we want to raise the issue and above all to make people feel the importance of the situation. Then, under the context of awareness raising, we present suggested solutions that we have found to solve this serious problem. We also need to add our own solution for an economical method of water desalination and purification. This will reduce the feeling of water scarcity without however being a definitive solution.